Extrahepatic biliary obstrution secondary to neuroendocrine tumor of the common hepatic duct. (2017) - Khan, Faraz A.; Stevens-Chase, Anastasia; Chaudhry, Rahman; Hashmi, Asra; Edelman, David; Weaver, Donald
Highlights: Extra hepatic biliary obstruction can be frequently caused by tumors. Differentiation between cholangiocarcinoma and an unusual bile duct tumor such as a neuroendocrine tumor (NET) is very difficult preoperatively. Prognosis of NET of the extrahepatic bile duct is dependent on the grade of the tumor however is markedly better than cholangiocarcinoma. Unusual biliary tumors can not be diferentiated preoperatively from cholangiocarcinoma. Abstract: Introduction: Primary neuroendocrine tumors (NET) of the extrahepatic biliary tree are a rare entity with less than 100 reported cases in the literature. Presentation of case: Here, we report a case of NET of the extrahepatic bile duct in a 64-year-old male patient presenting with painless jaundice, direct hyperbilirubinemia, and mildly elevated transaminases. Diagnostic workup with an ultrasound revealed dilation of the intrahepatic biliary ducts, without cholelithiasis or choledocholithiasis. Additional cross sectional imaging identified a stricture at the confluence of the common hepatic and cystic duct junction. Given lack of additional findings presumptive diagnosis of localized klatskin's tumor was made. The patient subsequently underwent resection of the common bile duct and roux-en-y hepaticojejunostomy reconstruction. Final pathologic diagnosis showed G2 well-differentiated NET of the extrahepatic bile duct, measuring 1.3 × 1.1 × 1 cm. Discussion: When a patient is evaluated for a primary bile duct neoplasm, differentiation between cholangiocarcinoma and an unusual bile duct tumor, such as a NET is very difficult before surgical resection and histologic review. Conclusion: NET of the extrahepatic biliary tree are a rare entity. Typical presentation is with painless jaundice and other symptoms related to obstruction of the biliary tree and the diagnosis is usually made post-operatively.